2015
DOI: 10.1186/s13058-015-0633-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss, with or without exercise, on body composition and sex hormones in postmenopausal women: the SHAPE-2 trial

Abstract: IntroductionPhysical inactivity and overweight are risk factors for postmenopausal breast cancer. The effect of physical activity may be partially mediated by concordant weight loss. We studied the effect on serum sex hormones, which are known to be associated with postmenopausal breast cancer risk, that is attributable to exercise by comparing randomly obtained equivalent weight loss by following a hypocaloric diet only or mainly by exercise.MethodsOverweight, insufficiently active women were randomised to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 52 publications
3
85
0
Order By: Relevance
“…These results are in accordance with the results of a meta-analysis by Gourlan et al and an earlier study of our study group (van Gemert et al, 2015, Gourlan et al, 2011). Gourlan et al summarized the long-term maintenance of interventions promoting physical activity levels in people with overweight and obesity; and they showed that exercise interventions, varying from three weeks to six months, were successful in maintaining physical activity levels after the intervention has ended (Gourlan et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in accordance with the results of a meta-analysis by Gourlan et al and an earlier study of our study group (van Gemert et al, 2015, Gourlan et al, 2011). Gourlan et al summarized the long-term maintenance of interventions promoting physical activity levels in people with overweight and obesity; and they showed that exercise interventions, varying from three weeks to six months, were successful in maintaining physical activity levels after the intervention has ended (Gourlan et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…The primary goal of the SHAPE-2 trial was to study the effects of 5–6 kg weight loss induced by a hypocaloric diet or mainly by exercise on postmenopausal serum sex hormone levels, associated with breast cancer risk(van Gemert et al, 2015, van Gemert et al, 2013). The mainly exercise intervention was combined with a small caloric intake restriction to ensure the intended weight loss in this short time-frame.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the SHAPE-2 trial on body composition and fitness are published separately (18). To summarize, both groups attained the weight loss goal.…”
Section: Body Composition and Fitnessmentioning
confidence: 99%
“…The primary outcome was changed in serum sex hormone levels (18). Here, we report on inflammatory markers [highsensitive (hs)CRP, IL6] and adipokines (leptin and adiponectin).…”
Section: Design Overviewmentioning
confidence: 99%
“…The incidence of breast cancer has increased over the past 30 years due to a variety of factors from improved screening methods, longevity, and exposure to carcinogens to changes in lifestyle [2]. However, the mortality rate is decreasing, reflecting the benefits of early detection, screening and improvements in treatment [3].…”
Section: Introductionmentioning
confidence: 99%